2022
DOI: 10.48550/arxiv.2201.02638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining Warm Dark Matter and Pop III stars with the Global 21-cm Signal

Joshua J. Hibbard,
Jordan Mirocha,
David Rapetti
et al.

Abstract: Upcoming ground and space-based experiments may have sufficient accuracy to place significant constraints upon high-redshift star formation, Reionization, and dark matter (DM) using the global 21-cm signal of the IGM. In the early universe, when the relative abundance of low-mass DM halos is important, measuring the global signal would place constraints on the damping of structure formation caused by DM having a higher relic velocity (warm dark matter, or WDM) than in cold dark matter (CDM). Such damping, howe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Figure 1 shows the cosmic thermal evolution (left panel) and the 21-cm signal (right panel) for the best-fitting values of the seven parameters of the model described above, when the model is fit to the EDGES measurement, assuming a constant 50 mK uncertainty across the frequency band (see also Hills et al 2018;Mirocha & Furlanetto 2019;Chatterjee et al 2021;Hibbard et al 2022). The best-fitting parameter values are listed in Table 1.…”
Section: The 21-cm Absorption Profilementioning
confidence: 99%
“…Figure 1 shows the cosmic thermal evolution (left panel) and the 21-cm signal (right panel) for the best-fitting values of the seven parameters of the model described above, when the model is fit to the EDGES measurement, assuming a constant 50 mK uncertainty across the frequency band (see also Hills et al 2018;Mirocha & Furlanetto 2019;Chatterjee et al 2021;Hibbard et al 2022). The best-fitting parameter values are listed in Table 1.…”
Section: The 21-cm Absorption Profilementioning
confidence: 99%
“…The first generation of stars, commonly referred to as the population III (Pop III) stars (Bromm & Larson 2004;Klessen 2019), are expected to have a strong effect on the high-redshift IGM, and, thus, the 21-cm signal from cosmic dawn (Cohen et al 2016;Mirocha et al 2018;Mebane et al 2018;Tanaka et al 2018;Schauer et al 2019;Mebane et al 2020;Muñoz et al 2021;Tanaka & Hasegawa 2021;Hibbard et al 2022). It has been shown that the efficiency and rate of star formation for the Pop III stars strongly impact the depth of the 21-cm global signal absorption trough (Yajima & Khochfar 2015;Cohen et al 2018;Mebane et al 2018;Mirocha & Furlanetto 2019;Schauer et al 2019;Chatterjee et al 2020;Muñoz et al 2021;Reis et al 2021a).…”
Section: Introductionmentioning
confidence: 99%